An Integrative Review of Sistah Circles in Empirical Research. (June 2023) - Jones, Martinque K.; Davis, Shardé M.; Gaskin-Cole, Gabriella
Sistah circles are spaces shared by Black women who share similar goals, exchange resources (e.g., support), and invest in developing strong relational bonds over time. Considering the significance of sistah circles for Black women's wellness and survival, in this study we examined how this phenomenon has been researched in the social sciences literature and, in turn, offered a more refined conceptual definition and framework that will direct future research on this topic. Specifically, we completed an integrative review of empirical studies on sistah circles using social science databases and search engines to identify relevant literature. Articles included for review met the following criteria: (a) published between 2000 and 2020, (b) analyzed empirical data, (c) were composed of Black women participants, and (d) mentioned Black women groups or friendships. Qualifying sources ( N = 45) were organized into a taxonomy of three types of sistah circles: health-focused, social, and professional. We also analyzed sample characteristics, research methods, and publication trends across all of the articles included in the review. Based upon our taxonomy and results of our review, we highlight the strengths and limitations of the current scholarship focused on Black women's sistah circles and offer suggestions regarding future research and practice. Additional online materials for this article are available on PWQ's website at http://journals.sagepub.com/doi/suppl/10.1177/03616843231154564